2009
DOI: 10.1111/j.1467-954x.2008.01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Connections: An Exploration of the Place of Mobile Phones in Friendship Relations

Abstract: This paper explores the place and meaning of mobile phones within friendship relations amongst young Pakistani-British women and men. In particular it focuses on the ways in which friendship relations are transformed and reconfigured through new mobile phone technologies; and how "doing" friendship on the mobile uncovers significant insight into contemporary youth cultures of masculinity and femininity. Although the majority of young people of the "multimedia generation" have fully engaged with the mobile tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In the present study, PUMP scale score was higher among the students having alover (p<0.05). Previous studies have also reported similar results (Green & Singleton, 2009), (Sara Berg, 2003).…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, PUMP scale score was higher among the students having alover (p<0.05). Previous studies have also reported similar results (Green & Singleton, 2009), (Sara Berg, 2003).…”
Section: Discussionsupporting
confidence: 76%
“…There remains controversy about whether such differences are innate or acquired (Gneezy, Leonard, & List, 2009), though there is by now strong evidence of hormonal factors in some such gender differences (Apicella et al, 2008;Chen, Katusczak, & Ozdenoren, 2009;Dreber et al, 2009). Outside the laboratory there is evidence from surveys that men and women may display differences in the use of communications technologies such as mobile phones (Green & Singleton, 2009;Igarashi, Takai, & Yoshida, 2005;Lemish & Cohen, 2005), as well as other evidence about clustering in social behavior resulting from different behavior patterns (Babcock & Leschever, 2003). However, these surveys mostly rely on self-reported behavior and many fewer studies to date have investigated more objective evidence such as telephone billing records (Smoreda & Licoppe, 2000;Wajman, Bittman, & Brown, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Like mobile technologies, social networking sites are often accused of 'displacing' real relationships. More nuanced arguments (Green and Singleton 2009;Larsen et al 2004) acknowledge the potential for temporal flexibility in creating and maintaining relationships as supported by Licoppe's (2004) (Fischer 1992). Externalities include things such as increased demand of telecommunications networks, thus requiring expensive upgrades, the cost of which is frequently passed on to consumers.…”
Section: Mobile Phones: the Overlap Of Social And Technical Spheresmentioning
confidence: 99%
“…Turkle states that technology is significant because it "proposes itself as the architect of our intimacies" (2011: 1). It also provides space for identity work and a platform through which to shape and communicate the self (Green and Singleton 2009;Gershon 2010;Turkle 2011). For Turkle (1996, cyberspace makes possible the construction of fluid identities that strain the notion of authenticity.…”
Section: Electronic Media Identity and Spacementioning
confidence: 99%
See 1 more Smart Citation